Numerical Investigation of the Landslide and Its Surge: A Case Study of the Gongjiafang Landslide in the Three Gorges Reservoir Area - Yunyun Fan; Dongyang Ma; Xu Sun (Geofluids)
Once the slope in the near bank area enters the state of failure, a geological disaster chain caused by landslide and its generated surge occurs very likely. In this study, a two-layer depth-averaged model was used to describe the disaster chain. The HLL (Harten-Lax-van Leer) finite volume method was used for numerical simulation and analysis. Meanwhile, the linear interpolation technique was employed to obtain second-order accuracy. The numerical results of the analytical examples reflect the movement characteristics of the two-layer fluid and verify the correctness of the numerical model. On the basis of numerical verification, the Gongjiafang landslide and its surge were simulated and analyzed. In the early stage, the deformation of the underwater geomaterials disturbed the water, forming the prototype of the surge, and then the landslide movement promoted the rapid development of the surge. After the landslide was deposited, the surge continued to travel forward and formed the largest form near the opposite bank. The numerical simulation is applicable to complex terrain and reveals some mechanisms and characteristics of the disaster chain. Compared with empirical methods, the numerical model adopted could reproduce the process of disasters chain more accurately and effectively and then improve the understanding of the disaster chain. It is feasible that the proposed numerical model can be applied under approximate plane strain conditions but is no longer applicable under 3D conditions. This work can provide reference for further research on disaster chain caused by landslide.